Optimising rhinoplasty outcomes in patients with thick skin - Catrin Wigley; Jonathan Sutton; Nicholas Eynon-Lewis; Rajan Uppal (JPRAS Open, 2025)
Background: Performing rhinoplasty in patients with a thick skin often presents as a challenge. This article describes an assessment tool to (1) classify patients according to the thickness of their skin and (2) to demonstrate the clinical application of this classification for the benefit of patients before Rhinoplasty. Methods: 166 patients underwent open rhinoplasty and were graded according to the Nasal Skin Thickness Scale (NSTS). Those patients graded as having thicker skin were selected for an acid peel before surgery. Preoperative and 6-month postoperative rhinoplasty outcome evaluation (ROE) score were collected to assess outcomes as these are a validated patient reported outcome measure. Pearson chi-square test was used to determine statistically significance of the postoperative groups. Results: All patients with thick skin (grade 3) or above were offered a preoperative skin acid peel. A total of 42 patients received this peel. There was a mean improvement of 6.4 of the nose outcomes in patients who had no peel. The mean nose improvement in patients receiving the peel was 6.6 (p < 0.001). This indicates a marginal improvement of outcome in patients who had an acid peel before rhinoplasty. Conclusions: This nasal skin thickness scale provides a simple framework for classifying nasal skin thickness. Skin thickness helps us identify patients who would benefit from optimisation of their skin before surgery to get the best results. In this case optimisation of the skin was undertaken with chemical peels. The acid peel helped shrink the skin and improve outcomes after rhinoplasty. This classification helps select patients who have thick skin and can be warned about swelling, lack of definition and the possible need for preconditioning.